THE RELATIONSHIP OF SELF-ESTEEM AND SCHOOL CLIMATE WITH BULLYING BEHAVIOR AT AL MANAR PRIVATE SMP SCHOOL MEDAN - Mahmuddin Ujung; Nefi Darmayanti; Yudistira Fauzy Indarawan (RADJA PUBLIKA, 2024)
This research aims to determine the relationship between self-esteem and school climate and bullying behavior at Al Manar Private Middle School, Medan. This type of research is quantitative research with correlational methods.The population in this study was 150 students with the sampling technique being total sampling and the sample in this study was 120 students by screening students who behaved in bullying ways and the results of the trial. The measuring tool used is a Likert scale to measure Self-Esteem and School Climate with Bullying Behavior. The data analysis method used in this research is multiple regression analysis. The subjects in this research were students at Al Manar Medan with the research results showing that: (1) There is a significant negative relationship between self-esteem and bullying behavior as indicated by the coefficient = -0.525; p=0.001 p<0.05 results showed that self-esteem had a predictive power for bullying behavior of 27.5%. (2) There is a significant negative relationship between school climate and bullying behavior in Al Manar Medan which is indicated by = -0.546; p=0.000 p<0.05 The results showed that school climate had a predictive power on the emergence of bullying behavior of 29.8%. (3) There is a significant relationship between self-esteem and school climate and bullying behavior as indicated by the coefficient F=12.039 R= -0.560 while =0.313 with p=0.000 P<0.05. Together, self-esteem and school climate have a predictive power for the emergence of bullying behavior of 30.3%. From these results it is known that there is still a 69.7% contribution from other factors or variables to the formation of bullying behavior. From the results of this research, the proposed hypothesis is declared accepted.